Lipids Oxidative Stability and Microbial Shelf Life Quality of Licorice (Glycyrrhiza glabra L.) Extract Supplemented Chicken Patties - MN Aslam; M Sohaib; AU Khan; S Ali; A Amjad; S Ahmed (Brazilian Journal of Poultry Science, 2020)
ABSTRACT The current study envisaged to evaluate the role of licorice (Glycyrrhiza glabra L.) extract on lipid oxidation, quality attributes, sensorial as well as microbial stability of chicken meat patties at refrigerated (4 ˚C) storage. Accordingly, 4 levels of licorice extract were added @0.25, 0.5, 1.0 and 1.25% in chicken patties development process along with positive (0.25% butylatedhydroxyanisole) and negative control (without antioxidant). The developed patties were cooked and subjected to thiobarbituric acid reactive substances (TBARS), total phenolics (TPC), ferric reducing antioxidant power (FRAP), color, pH, sensory evaluation, total plate count (TPC) and Escherichia coli analysis at 0, 3rd and 7th day of storage. The findings indicated that the addition of licorice extract decreased malonaldehyde (MDA) generation along with higher pH and redness of patties (p≤0.05). The lowest MDA reported in T5 (1.25g LE/kg meat) was 0.63±0.04 whereas, the highest in T0 (control) was 0.90±0.02 that increased to 1.59±0.06 and 2.28±0.06 at the completion of the study. Also, the microbial load of chicken patties declined with treatments as indicated by the total plate count compared to the control. Conclusively, licorice extract incorporation in chicken patties is a pragmatic approach to improve oxidative stability, quality attributes and extended shelf life with preservation effect.